Isolation and Cytotoxic Activity of Acyclic Triterpene Callicarpenol from Callicarpa macrophylla - Chung, Ill-Min; Ali, Mohd.; Upadhayay, Kumud; Ahmad, Ateeque (Asian Journal of Chemistry, 2016)
The dried fruit tissue of Callicarpa macrophylla, one new acyclic triterpene, 2,6,14,18,22-pentamethyl-n-tetracos-9-en-17a-ol-27-oic acid (1) was isolated along with known compounds b-sitosterol, oleanolic acid and b-sitosterol-3-O-b-D-glucoside. The structure of the new compound was elucidated by 500 MHz NMR using 1D and 2D spectral methods, viz., 1H, 13C, 1H-1H COSY and HETCOR aided by EIMS, CIMS, FABMS and IR, UV and chemical methods. The compound 1 was found to have cytotoxic effects against P388 murine leukemia cells, the b-sitosterol and b-sitosterol-3-O-b-D-glucoside had no cytotoxicity.